Efektivitas Sediaan Spray Ekstrak Bunga Tembelekan (Lantana camara L.) sebagai Repellent Nyamuk Aedes Aegypti - I Gusti Agung Ayu Kusuma Wardani; Ni Putu Sintia Rahayu; Ni Nyoman Wahyu Udayani (Jurnal Ilmiah Medicamento, 2022)
The Aedes aegypti mosquito is the main vector of dengue fever. Controlling the spread of mosquitoes by using plants is an alternative that can be done to avoid the toxicity of chemical insecticides. One of the plants that can be used in mosquito control is tembelekan flower. This study aims to determine the effectiveness of the spray preparation of Tembelekan flower extract (Lantana camara L.) as a repellent. The design of this study was a randomized control group posttest only design. This study used 100 Aedes aegypti mosquitoes which were divided into 5 treatment groups. The extract was made in three concentration variations, namely 13%, 15%, and 17%. The results showed that P2 (positive control) and P5 (extract 17%) had the same effectiveness as a repellent, with a significant value of 0.316 (p>0.05). Based on the research that has been done, it can be concluded that the preparation of mosquito repellent spray from tembelekan flower extract with a concentration of 17% is the most effective concentration as a repellent in this study.